A preliminary study on the prevalence of infectious bovine rhinotracheitis virus infection in buffaloes in Malaysia. - Saw, Plei Saw; Ibrahim, A. Latif; Abdul Rahman, Sheikh Omar (Philippine Society of Animal Science, 1983)
A serological survey on the prevalence of infectious bovine rhinotracheitis in Malaysia showed that about 67% of the buffaloes had antibody to infectious bovine rhinotracheitis virus. Neutralizing antibody was detected in 122 of the 180 serum samples from buffaloes. At Universiti Pertanian farm the number of seropositive buffalo calves (81.8%) and buffalo cows (91.3%) were higher than the heifers (39.5%). The role of infectious bovine rhinotracheitis virus as a possible causative agent of calf mortality and infertility in buffaloes is discussed.